Alterations in the metabolism of hamster tracheas in organ culture after infection by virulent Mycoplasma pneumoniae. - Hu, P C (1975)
Exposure of hamster tracheal rings in organ culture to virulent Mycoplasma pneumoniae organisms leads to alterations in macromolecular biosynthesis and metabolic activity of the respiratory epithelial cells. Avirulent organisms derived from the same parent strain do not produce these effects. During the course of infection by virulent mycoplasmas, tracheal rings show an initial increase in [14C]galactose uptake followed by a significant decline as infection progresses which is also accompanied by abnormal processing of galactose as evidenced by amounts of 14CO2 released. Parallel decreases in the rate of [3H]orotic acid and [3H]amino acid uptake are observed. Within 24 h after infection of tracheal rings by virulent mycoplasmas, inhibition of host cell ribonucleic acid and protien synthesis is evident. Ribonucleic acid synthesis in infected cells, analyzed by gel electrophoresis, is reduced by 80% at 48 h and is negligible by 96 h. The course of mycoplasma infection can be interrupted or reversed by erythromycin after the initial mycoplasma-host cell interaction since addition of erythromycin 24 h or earlier after infection prevents the onset of abnormal orotic acid uptake. However, 48 h after infection, rescue of host cells by erythromycin cannot occur and cytopathology becomes evident. These data suggest that mediation of host cell injury requires continued protein synthesis by attached mycoplasmas, and the primary effect of mycoplasma infection on tracheal organ culture may be at a transcriptional or translational level.